2020
DOI: 10.1101/2020.05.31.115444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual gating of a brainstem reflex facilitates speech understanding in human listeners

Abstract: 14Navigating "cocktail party" situations by enhancing foreground sounds over irrelevant background 15 information is typically considered from a cortico-centric perspective. However, subcortical circuits, 16 such as the medial olivocochlear reflex (MOCR) that modulates inner ear activity itself, have ample 17 opportunity to extract salient features from the auditory scene prior to any cortical processing. To 18 understand the contribution of auditory subcortical nuclei and the cochleae, physiological 19 record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Efferent-induced changes in human subcortical auditory function have, by necessity, almost exclusively been assessed through non-invasive objective measurements. Some reports have demonstrated that otoacoustic emissions (i.e., proxy measures of outer hair cell function) are modulated online by attention (Wittekindt et al, 2014;Smith and Cone, 2015;Hernandez-Perez et al, 2021) or through short-or long-term training (Perrot et al, 2006;de Boer and Thornton, 2008;Bidelman et al, 2014Bidelman et al, , 2016Bidelman et al, , 2017. Other reports using similar methodologies have failed to replicate these findings (Stuart and Butler, 2012;Francis et al, 2018;Jedrzejczak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Efferent-induced changes in human subcortical auditory function have, by necessity, almost exclusively been assessed through non-invasive objective measurements. Some reports have demonstrated that otoacoustic emissions (i.e., proxy measures of outer hair cell function) are modulated online by attention (Wittekindt et al, 2014;Smith and Cone, 2015;Hernandez-Perez et al, 2021) or through short-or long-term training (Perrot et al, 2006;de Boer and Thornton, 2008;Bidelman et al, 2014Bidelman et al, , 2016Bidelman et al, , 2017. Other reports using similar methodologies have failed to replicate these findings (Stuart and Butler, 2012;Francis et al, 2018;Jedrzejczak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing Activity (HA-EEG): The raw electroencephalogram (EEG) data was recorded from 61 healthy adults using 62 electrodes [58]. The participants were either actively listening to individual words over headphones (active condition) or watching a silent video and ignoring the speech (passive condition).…”
Section: Datasetsmentioning
confidence: 99%